PENGARUH PJBL TERHADAP PEMAHAMAN SISWA PADA MATERI SISTEM TATA SURYA DI KELAS 4 SDN SUKAMAJU - Safitriyanah, Nur; Mauliate Lumbantoruan, Cahyani; Humairah Hamzah, Najwa; Bulan Nurkhoir, Wafiq; Nur Fadilah, Devia; Gustian Nugraha, Rana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The entire population was used as research because the saturated sampling technique was used. This study aims to determine how the application of the project-based learning (PjBL) model impacts students' understanding of the solar system material in grade IV of SDN Sukamaju. The background of this study lies in the fact that students have a low conceptual understanding of abstract science material and that teachers still dominate learning. Therefore, a learning model that is able to actively involve students in the learning process is needed. One of them is the PjBL model. This experiment was conducted using a pretest-posttest group design. This study was attended by all 22 students in grade IV of SDN Sukamaju. Because the saturated sampling method was used, the entire population was used as the research subject. Concept understanding tests given before learning (pre-test) and after the application of the PjBL model in cycle II (post-test) were the research tools. To determine whether there was an increase in student understanding, the data obtained were analyzed quantitatively by comparing the average values ​​before and after the test. The results showed that the application of the PjBL model improved students' understanding of the solar system material. The results show that the project-based learning model can be used as an alternative learning method to improve the quality of science learning in elementary schools, especially in improving students' conceptual understanding.